ANALISIS PEMBELAJARAN SAINTIFIK DALAM PENDIDIKAN ISLAM - Nur Asyiah Bulqist Rahman; Ani Khoitotun Nisa; Sedya Santosa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Islamic education learning aims to develop students' morals, morals and spirituality, as well as help students understand the teachings of Islam and apply them in everyday life. In Islamic education learning, the scientific learning approach can be used to help students understand religious teachings more deeply and apply them in everyday life. The methodology used in this article is literature research or literature review. The author searches and selects literature related to scientific learning and Islamic education from various sources such as journals, books, articles, and websites. After that, the author processes the information found to be analyzed and associated with scientific learning in Islamic education. The results show that scientific learning is a learning approach that allows students to develop critical thinking skills and find solutions to problems using scientific methods. In religious learning, Curriculum 2013 prioritizes religious learning that touches on aspects of students' daily lives. Students are invited to develop an understanding of religious teachings that are relevant to everyday life and apply them in everyday life. The learning process with a scientific approach uses 5 M steps in learning activities: observing, questioning, gathering information (experimentation), associating (processing information), and communicating.